Weak Markets, Strong Teachers: Recession at Career Start and Teacher Effectiveness - Markus Nagler; Marc Piopiunik; Martin R. West (Center for Economic Studies and ifo Institute (CESifo), 2015)
How do alternative job opportunities affect teacher quality? We provide the first causal evidence on this question by exploiting business cycle conditions at career start as a source of exogenous variation in the outside options of potential teachers. Unlike prior research, we directly assess teacher quality with value-added measures of impacts on student test scores, using administrative data on 33,000 teachers in Florida public schools. Consistent with a Roy model of occupational choice, teachers entering the profession during recessions are significantly more effective in raising student test scores. Results are supported by placebo tests and not driven by differential attrition.
Keywords: E32; H75; I20; J24; 330; teacher value-added; talent allocation; business cycle; Roy model